Sulfur-doped g-C3N4/g-C3N4 isotype step-scheme heterojunction for photocatalytic H2 evolution. (10th August 2022) - Jiang, Jizhou; Xiong, Zhiguo; Wang, Haitao; Liao, Guodong; Bai, Saishuai; Zou, Jing; Wu, Pingxiu; Zhang, Peng; Li, Xin
Highlights: A new-fashioned g-C3 N4 -based isotype step-scheme heterojunction is fabricated by liquid sulfur-mediation and pyrolysis. The liquid-sulfur is conducive to the full contact between sulfur species and exfoliated g-C3 N4 . The pyrolysis achieves S-doping and abundant pores due to S-vapor self-gas foaming effect. This isotype step-scheme heterojunction shows high photocatalytic HER activity. Abstract: The rational fabrication of an efficient heterojunction is critical to the enhancement of photocatalytic hydrogen (H2 ) evolution performance. Herein, a new-fashioned graphitic-carbon nitride (g-C3 N4 ) based isotype step-scheme (S-scheme) heterojunction composed of sulfur-doped and sulfur-free active sites is developed by liquid sulfur-mediation of exfoliated g-C3 N4 . Particularly, the liquid sulfur not only contributes to the full contact between sulfur species and exfoliated g-C3 N4, but also creates sulfur-doping and abundant pores, since self-gas foaming effect of sulfur vapor. Moreover, the S-doped and S-free active sites located in the structural unit of C3 N4 jointly construct a typical sulfur-doped g-C3 N4 /g-C3 N4 isotype step-scheme heterojunction, which endows highly efficient photocatalytic reaction process. Therefore, the optimal sample possesses remarkable photocatalytic H2 evolution activity (5548.1 μmol g −1 h −1 ) and robust durability. Most importantly, the investigation will open up a new path for the exploration of other carbon-based isotype S-scheme heterojunctions. Graphical abstract: Image, graphical abstract